Integrating Social Determinants of Health into Primary Care Clinical and Informational Workflow during Care Transitions. Issue 2 (4th July 2017) - Hewner, Sharon; Casucci, Sabrina; Sullivan, Suzanne; Mistretta, Francine; Xue, Yuqing; Johnson, Barbara; Pratt, Rebekah; Lin, Li; Fox, Chester
Context: Care continuity during transitions between the hospital and home requires reliable communication between providers and settings and an understanding of social determinants that influence recovery. Case Description: The coordinating transitions intervention uses real time alerts, delivered directly to the primary care practice for complex chronically ill patients discharged from an acute care setting, to facilitate nurse care coordinator led telephone outreach. The intervention incorporates claims-based risk stratification to prioritize patients for follow-up and an assessment of social determinants of health using the Patient-centered Assessment Method (PCAM). Results from transitional care are stored and transmitted to qualified healthcare providers across the continuum. Findings: Reliance on tools that incorporated interoperability standards facilitated exchange of health information between the hospital and primary care. The PCAM was incorporated into both the clinical and informational workflow through the collaboration of clinical, industry, and academic partners. Health outcomes improved at the study practice over their baseline and in comparison with control practices and the regional Medicaid population. Major Themes: Current research supports the potential impact of systems approaches to care coordination in improving utilization value after discharge. The project demonstrated that flexibility in developing the informational and clinical workflow was critical in developing a solution that improved continuity during transitions. There is additional work needed in developing managerial continuity across settings such as shared comprehensive care plans. Conclusions: New clinical and informational workflows which incorporate social determinant of health data into standard practice transformed clinical practice and improved outcomes for patients.